Assessment of the regenerative potential of allogeneic periodontal ligament stem cells in a rodent periodontal defect model. (11th July 2013) - Han, J.; Menicanin, D.; Marino, V.; Ge, S.; Mrozik, K.; Gronthos, S.; Bartold, P. M.
<x xml:space="preserve">Abstract</x> Background and Objective The complex microenvironment of the periodontal wound creates many challenges associated with multitissue regeneration of periodontal lesions. Recent characterization of mesenchymal stem cell‐like populations residing in periodontal ligament tissues has shown that these cells exhibit features of postnatal stem cells. Despite these advances, a lack of consistency in design of preclinical studies and a limited study of allogeneic transplantation applications has restricted our understanding of their clinical utility in the treatment of periodontal disease. The aim of this study was to assess the regenerative potential of allogeneic periodontal ligament stem cells (PDLSCs) in a rat periodontal fenestration defect mode and to identify an optimal end time‐point suitable for quantitative assessment of tissue regeneration. Material and Methods Periodontal fenestration defects, created in Sprague Dawley rats, were treated with allogeneic PDLSCs seeded onto Gelfoam® (Absorbable gelatin sponge; Pharmacia Corporation, Kalamazoo, MI, USA) or with Gelfoam® alone, or remained untreated. Experimental rats were killed at 7, 14, 21 or 28 d after surgery and the tissues were processed for immunohistochemical and histomorphometric examination. Results Defects treated with PDLSCs showed significantly greater percentage bone fill and length of new bone bridge compared with the untreated group or the group treated withGelfoam® alone on days 14 and 21. Similarly, a statistically significant difference was achieved within specimens retrieved on day 21 for analysis of regeneration of cementum/periodontal ligament (PDL)‐like structures. Conclusion The present investigation shows that allogeneic PDLSCs have a marked ability to repair periodontal defects by forming bone, PDL and cementum‐like tissue in vivo. The results suggest that treatment periods of 14 and 21 d are optimal end time‐points for quantitative assessment of periodontal regeneration within the rodent fenestration‐defect model utilized in the present study.